Formulas for Income Elasticity of Demand & Cross Elasticity of Demand

Note by eleanor.adamandi, updated more than 1 year ago More Less
 Created by jackexamtime almost 7 years ago Copied by eleanor.adamandi almost 7 years ago
814
1

Description

Income Elasticity of Demand & Cross Elasticity of Demand both have a formula laid out to help you calculate them

Resource summary

Page 1

$\frac{\[\frac{(Change in Q)}{.5(Q1 + Q2)}$}{$\frac{(Change in Y)}{.5(Q1 + Q2)}$}\]

Where:Change in Q = Difference between the original quantity demanded and the new quantity demandedChange in Y = Difference between the original income and the new incomeQ1 = Original quantity demandedQ2 = New quantity demandedY1 = Original incomeY2 = New income This formula can be simplified to:

(Change in Q) X (Y1 + Y2)(Change in Y)    (Q1 + Q2)

Formula for Calculating YED

Formula for Calculating YED

$\frac{\[\frac{(Change in Q(X))}{.5(Q1(X) + Q2)}$}{$\frac{(Change in P(Y))}{.5(P1(Y) + P2(Y))}$}\]

Where:Change in Q(X) = Difference between the original quantity demanded of Good X and the new quantity demanded of Good XChange in P(Y) = Difference between the original price of good Y and the new price of good Y Q1(X) = Original quantity demanded of good XQ2(X) = New quantity demanded of good XP1(Y) = Original price of good YP2(Y) = New price of good Y

Calculating YED

Calculating CED

Similar

Income Elasticity of Demand
27. Economic Development & Growth
Shifts in the Supply Curve
Economic Development & Growth
Economic Development & Growth
Supply
Equilibrium
Price Elasticity of Demand
Economic Development and Growth
Excess Demand & Excess Supply
Supply